PELATIHAN PENGOLAHAN BACON DAN KERUPUK KULIT BABI YANG BEBAS PENYAKIT ZOONOSIS DI DESA PENFUI TIMUR, KECAMATAN KUPANG TENGAH - Meity Marviana Laut; Putri Pandarangga; Nemay Ndaong (Universitas Nusa Cendana, 2021)
The limited income for the majority of the community in Penfui Timur has an impact on the lack of average daily protein consumption. The women group of GMIT Ebenhezer-Matani is a group of housewives who plays an important role in improving nutrition to the family welfare. The program was offered as part of increasing family nutrition through protein consumption as well as improvement of family income. There are three phases of the program, which are direct extension and training, accompaniment and evaluation. During extension, participants were informed about how to choose qualified and healthy meat, the storage and preservation as well as the use of hazardous substances in meat preservation. Furthermore, participants were trained on bacon and skin cracker processing through washing, scalding, liming, boiling, marinating, cutting, drying and frying. After the demonstration, participants were given materials and tools to start the production. In this phase, participants were also trained to do simple bookkeeping by calculating production costs and profits. Processed bacon and skin crackers produced by the participants met the requirements organoleptically. The bacon has a bright colour with a distinctive smoky aroma, while the skin cracker is brownish yellow, crunchy and savoury even though the size varies. In conclusion, this program has great potential as a business opportunity to improve the family economy as well as family nutrition.